In‐Situ Electrodeposition of Rhodium nanoparticles Anchored on Reduced Graphene Oxide nanosheets as an Efficient Oxygen Reduction Electrocatalyst - Sookhakian, Mehran; Tong, Goh Boon; Alias, Yatimah (Wiley, 2020)
A simple, versatile, and cost-effective one-pot electrochemical deposition is used to fabricate rhodium (Rh) nanoparticles decorated surface of reduced graphene oxide (rGO) functionalized glassy carbon electrode (GCE) for oxygen reduction reaction (ORR) in alkaline media. The chemical and physical structure of the sample is probed via transmission electron microscopy, rotating disk electrode (RDE), X-ray photoelectron spectroscopy, linear sweep voltammetry, and Raman spectroscopy. The synergistic effects between the unique properties of Rh nanoparticles and rGO creates such innovative hybrid that exhibits a catalytic activity comparable to that of the commercial platinum electrocatalyst (Pt/C). As a result, the as-electrodeposited Rh@rGO hybrid exhibits outstanding ORR activity in alkaline media, as evidenced by a larger diffusion-limited current, greater positive onset potential, much better stability and methanol tolerance than Pt/C under the same conditions. © 2020 John Wiley & Sons, Ltd.